Specific and Sensitive Detection of the Pear Scab Fungus Venturia nashicola by SYBR Green Real-Time PCR - Yun, Yeo Hong; Yoon, Seong Kwon; Jung, Jae Sung; Kim, Seong Hwan (Journal of microbiology and biotechnology, 2015)
A new improved PCR method has been developed for the rapid, reliable, and sensitive detection of Venturia nashicola, a destructive pathogen of scab disease in Japanese pear. The translation elongation factor-1 alpha gene-derived PCR primers specifically amplified a 257-bp-sized DNA band of the target gene from the genomic DNA of V. nashicola. No amplicon was produced from the genomic DNA of other Venturia spp. and reference fungal species tested. With the high detection limit of 10 fg DNA content, our real-time method could be used for the quarantine inspection and field monitoring of V. nashicola.